Metaplastic carcinoma of breast - Dewasi, N; Bhattacharya, D; Sarker, PG; Das, M; Ghosh, S; Ghosh, TK (Journal of Pathology of Nepal, 2014)
Metaplastic carcinomas of breast are a heterogeneous group of malignant tumours in which part or all of the carcinomatous epithelium is transformed into a nonglandular (metaplastic) growth process. This rare neoplasm usually runs an aggressive course. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10320 Journal of Pathology of Nepal (2014) Vol. 4, 594-596